A 2+1 + 1 quadruple star system containing the most eccentric, low-mass, short-period, eclipsing binary known. Issue 2 (3rd December 2021) - Han, E; Rappaport, S A; Vanderburg, A; Tofflemire, B M; Borkovits, T; Schwengeler, H M; Zasche, P; Krolikowski, D M; Muirhead, P S; Kristiansen, M H; Terentev, I A; Omohundro, M; et al.
ABSTRACT: We present an analysis of a newly discovered 2+1 + 1 quadruple system with TESS containing an unresolved eclipsing binary (EB) as part of TIC 121088960 and a close neighbour TIC 121088959. The EB consists of two very low-mass M dwarfs in a highly eccentric ( e = 0.709) short-period ( P = 3.043 58 d) orbit. Given the large pixel size of TESS and the small separation (3_.^′′ 9) between TIC 121088959 and TIC 121088960 we used light centroid analysis of the difference image between in-eclipse and out-of-eclipse data to show that the EB likely resides in TIC 121088960, but contributes only ∼10 per cent of its light. Radial velocity data were acquired with iSHELL at NASA's Infrared Facility and the Coudé spectrograph at the McDonald 2.7-m telescope. For both images, the measured RVs showed no variation over the 11 d observational baseline, and the RV difference between the two images was 8 ± 0.3 km s −1 . The similar distances and proper motions of the two images indicate that TIC 121088959 and TIC 121088960 are a gravitationally bound pair. Gaia's large RUWE and astrometric_excess_noise parameters for TIC 121088960, further indicate that this image is the likely host of the unresolved EB and is itself a triple star. We carried out an SED analysis and calculated stellar masses for the four stars, all of which are in the M dwarf regime: 0.19 M⊙ and 0.14 M⊙ for the EB stars and 0.43 M⊙ and 0.39 M⊙ for the brighter visible stars, respectively. Lastly, numerical simulations show that the orbital period of the inner triple is likely the range 1–50 yr.